Tingkat Kepuasan Konsumen Terhadap Aplikasi KILOGS pada PT. Krakatau Jasa Logistik - Al Hidayat, Rahmat; Agustiani, Nurlaili; Akmal, Samsul (STIA Bengkulu, 2025)
This study aims to analyze the implementation of the KILOGS application in improving cargo tracking transparency and customer satisfaction at PT. Krakatau Jasa Logistik (KJL). This study uses a qualitative approach with a case study method. Data for this study came from two main sources, namely primary data and secondary data, using in-depth interviews, observations and documentation as data collection techniques. The data obtained were analyzed using the thematic analysis method using the Nvivo analysis tool. This technique is used to identify, analyze, and report patterns (themes) that emerge from qualitative data. The results of this study indicate that the implementation of the KILOGS application by PT. Krakatau Jasa Logistik significantly improves customer satisfaction by providing real-time tracking capabilities, automatic notifications and accurate information, thereby increasing transparency and customer trust. The application also succeeded in improving the company's operational efficiency by reducing tracking time, error frequency, and manual employee workload. However, the implementation of KILOGS faces challenges such as low digital customer literacy, difficult registration processes, and preferences for traditional